BMP2 and GDF5 for Compartmentalized Regeneration of the Scapholunate Ligament - Lui, Hayman; Vaquette, Cedryck; Denbeigh, Janet M.; Bindra, Randy; van Wijnen, Andre J.; Kakar, Sanjeev (Journal of Wrist Surgery, 2023)
Background Chronic injuries to the scapholunate ligament (SLIL) alter carpal kinematics and may progress to early degenerative osteoarthritis. To date, there is no consensus for the best method for SLIL reconstruction. This study aims to assess the use of growth factors (bone morphogenetic protein [BMP]2 and growth and differentiation factor 5 [GDF5]) for compartmentalized regeneration of bone and ligament in this multiphasic scaffold in a rabbit knee model.Case Description A total of 100 µg of BMP2 and 30 µg of GDF5 were encapsulated into a heparinized gelatin–hyaluronic acid hydrogel and loaded into the appropriate compartment of the multiphasic scaffold. The multiphasic scaffold was implanted to replace the native rabbit medial collateral ligament (n = 16). The rabbits were randomly assigned to two different treatment groups. The first group was immobilized postoperatively with the knee pinned in flexion with K-wires for 4 weeks (n = 8) prior to sacrifice. The second group was immobilized for 4 weeks, had the K-wires removed followed by a further 4 weeks of mobilization prior to sample harvesting.Literature Review Heterotopic ossification as early as 4 weeks was noted on gross dissection and confirmed by microcomputed tomography and histological staining. This analysis revealed formation of a bony bridge located within and over the ligament compartment in the intra-articular region. Biomechanical testing showed increased ultimate force of the ligament compartment at 4 weeks postimplantation consistent with the presence of bone formation and higher numbers of scaffold failures at the bone–tendon junction. This study has demonstrated that the addition of BMP2 and GDF5 in the bone–ligament–bone (BLB) scaffold resulted in heterotopic bone formation and failure of the ligament compartment.Clinical Relevance The implantation of a three-dimensional-printed BLB scaffold alone demonstrated superior biomechanical and histological results, and further investigation is needed as a possible clinical reconstruction for the SLIL.
Keywords: Bone-ligament-bone; BMP2; GDF5; scapholunate interosseous ligament; compartmentalized regeneration; rabbit knee joint